IMPLIKASI TANGGUNG JAWAB NOTARIS TERHADAP AKTA PERNYATAAN KEPUTUSAN RAPAT UMUM PEMEGANG SAHAM YANG DIBUAT DENGAN MENGGUNAKAN DOKUMEN PALSU - Tanjung, Adrian; Sudiro, Amad (UNES Law Review, 2023)
The purpose of this study is to critically analyze the quality of Supreme Court decisions in achieving justice and legal certainty in Indonesia. The Supreme Court is an important part of the justice system in upholding justice and providing legal security to the public. Nonetheless, the success of achieving the goals largely depends on the quality of the decisions made. Relevant Supreme Court decisions and a review of supporting literature were used in this qualitative research. This method allows for a thorough analysis of the components that affect the quality of decisions, such as the protection of human rights, equality before the law, equality of treatment, consistency in the interpretation and application of the law, and the guarantee of fair and clear legal protection.